Attraction to Carbon Dioxide from Feeding Resources and Conspecific Neighbours in Larvae of the Rhinoceros Beetle Trypoxylus dichotomus - Kojima, Wataru (Public Library of Science, 2015)

(untitled) (PLoS One)
Saprophagous (feeding on decaying matter) insects often use carbon dioxide (CO(2)) as a cue for finding food. Humus-feeding larvae of the giant rhinoceros beetle Trypoxylus dichotomus exhibit a clumped distribution in natural microhabitats, but the mechanisms driving the distribution were unknown. Herein, I examined whether larvae use CO(2) as a cue for fermented humus and aggregate in the vicinity of the food. I found that (i) larvae of T. dichotomus are strongly attracted to CO(2), (ii) larvae orient toward highly fermented humus when given a choice between highly and poorly fermented humus, (iii) the highly fermented humus emits more CO(2) than the poorly fermented humus, and (iv) larvae grow larger when fed highly fermented humus rather than poorly fermented humus. The clumped distribution of larvae is probably formed along the concentration gradient of CO(2) induced by heterogeneity of fermented organic materials in soil. My laboratory experiments also revealed that larvae are chemically attracted to each other. Moreover, CO(2) concentrations in soil were increased by the larval respiration, and small amounts of CO(2) (much less than emitted during respiration by a single larva) were sufficient for larval attraction. These results suggest that not only response to fermented food resources, but also respiratory CO(2) from conspecifics may lead to aggregation. Enhanced densities resulted in reduced weight gain under experimental conditions. However, exploiting a high-value resource at enhanced densities still led to greater body weight compared to individually exploiting a low-value resource. This demonstrates the adaptive value of the response to CO(2) sources in this species.